80.0k views
0 votes
Prove of each of the expressions bellow are equivalent by evaluating the expressions.

Given:g=3

Prove of each of the expressions bellow are equivalent by evaluating the expressions-example-1
User Ndemou
by
6.1k points

2 Answers

4 votes

Answer:

See below.

Explanation:

To prove these expressions are equivalent, we need to set the two expressions equal to each other in an equation and substitute 3 for g.

15(3) - 2(2(3) + 6) = 11(3) - 12

15(3) - 2(6 + 6) = 11(3) - 12

15(3) - 2(12) = 11(3) - 12

45 - 24 = 33 - 12

21 = 21

User Qammar Feroz
by
5.0k points
12 votes

Answer:

sove the equation and you'll get 20

User Laskdjf
by
5.3k points